IMPLEMENTASI METODE BUSINESS PROCESS REENGINEERING (BPR) PADA SISTEM PELAYANAN DATA PENDUDUK - M Arip Islahudin; Wiwien Hadikurniawati (JURNAL ILMIAH INFORMATIKA, 2022)
Kalimas Village is currently still using conventional methods in providing population data services so that the recording process takes a long time. The solution to overcome this is to create a web-based program that has features of recording and reporting population data. With this website, employees don't need books and Microsoft Word to make notes that happen twice. Business Process Reengineering (BPR) is a business approach that focuses on analyzing workflows or business processes that occur within an institution or organization. The author applies the BPR method to identify the workflow of the system that is running at the Kalimas Sub-District office and get an idea for creating a web-based application to help speed up the process of serving population data in Kalimas Sub-District. The results of this study are in the form of a population administration system to record SKTM, KTP, KK, Birth Certificates, Death Certificates, Transfer Certificates, and Coming Transfer Letters. Parties who can use this application are kelurahan employees, village heads, and admins. The application generated from this research has the benefit of making it easier for Kalimas Village employees to manage population data and making it easier for the Lurah to monitor the Kalimas Village population data.